Do glamour à política: Janaína Dutra em meandros heteronormativos - SAMPAIO, Juciana de Oliveira (2015)
This thesis focuses on the discussion of the constitution of travestis in the midst of the heteronormativity, analyzing social processes of development of knowledge, categorizations and practices aimed to summarize the experience of these subjects in their gender performances, with centrality in the life experience of Janaina Dutra (1960 -2004), an activist from Ceará considered the "first travesti lawyer in Brazil." Guided by the theoretical frameworks of gender, feminist and queer studies, I rebuild the life experience of this travesti in amid the analysis of normalization, which asks how is established the borders of difference. Understanding that the heteronormativity regulates the lives of individuals and that the social order is a sexual order, I call attention to the constitution of gender in the organization of social relations and how these differentiation axes are related to other social markers such as region, ethnicity, nationality, religion, social class. With this research, I intend to show, among other things, that the subjects are unstable and indeterminate, far from being fixed and self-evident.